La transformación en seres adversos: el caso de la jupaymula - Huamán Antonio, Timna Yulisa (2019)
A diversity of mythical and magical beings shape the Andean imaginary, groups of them are qualifed as negative due to the hostile action they manifest in their relationship with the inhabitants. In this article, the general features of these beings are exposed as result of the morphological transformation that aﬀects their original nature, which also implies changes in their habitual behavior and in the function;they perform as members of pacha. Likewise, the fgure of the jupaymula —character that syncretizes Andean and Hispanic mythical-religious conceptions— is emphasized, determining its characteristics, its procedure before, during and after the metamorphosis, from which it is concluded that its conversion is a sanction for infringing the moral principles of his community linked with incest. Tis corroborates that adverse beings, in most cases, were constituted as instruments used to exert social control.